An intramolecular cycloaddition of nitrones with tethered olefins: a versatile synthesis of hexahydro-3H-xantheno[1, 2-c]isoxazoles. Issue 26 (29th June 2016) - Rao, Y. Jayaprakash; Reddy, E. Pravardhan; Sridhar, B.; Lakshmi, J.K.; Reddy, B.V. Subba
Graphical abstract: Highlights: First report on the synthesis of 3 H -xantheno[1, 2- c ]isoxazoles by 1, 3-dipolar cycloaddition. This method is operationally simple and works with a diverse range of substrates. It is a highly diastereoselective. The products are useful to generate amino alcohols by reductive cleavage. These oxazolidines are novel scaffolds for biological screening. Abstract: A variety of isoxazolidine and isoxazoline derivatives have been prepared through a 1, 3-dipolar cycloaddition of alkene-tethered chromene-3-carbaldehydes with hydroxyl amines. This is the first example of the preparation of highly diastereoselective isoxazolidine derivatives from alkene appended chromene-3-carboxaldehyde. This method is operationally simple and works with a diverse range of substrates.